Clinicopathological significance of insulin-like growth factor-1 receptor expression in breast cancer - Şahin, Sevinç; Çakır, Aslı; Gönül, İpek Işık; Seçkin, Selda; Uluoğlu, Ömer (Edizioni Luigi Pozzi, 2020)
OBJECTIVE: Insulin-like growth factor 1 receptor (IGF1R) is a receptor protein tyrosine kinase that is claimed to be related with tumor development and progression of breast cancer with some conflicting results in the literature. The aims of the study are to investigate expression of IGF1R, and correlate with clinicopathological parameters to clarify the significance of IGF1R on breast cancer.MATERIAL AND METHODS: IGF1R and Ki67 were applied immunohistochemically to the tissue microarray sections of 370 female breast cancer patients. The results were correlated with clinical, prognostic, histopathological features, and other immunohistochemical findings [ER, PR, HER2, CK5/6, and CK14] statistically.RESULTS: IGF1R overexpression showed direct correlation with Ki67 index (P=0.028), HER2 positivity (P=0.001), mitotic count (P=0.004), tumor grade (P=0.015), and geographic necrosis (P=0.023); and negative correlation with ER positivity (P=0.003). There was statistically significant difference between IGF1R expression and the molecular subtypes (P<0.001), mostly HER2+ phenotype. IGF1R expression was found to be higher in invasive ductal carcinoma (IDC) than invasive lobular carcinoma (ILC) (P=0.036). Both IGF1R and Ki67 expression were negatively correlated with disease-free survival (DFS) (P=0.020, P=0.023, respectively) and overall survival (OS) [P<0.001, each] rates. The inverse association between IGF1R overexpression and OS rate was also supported by multivariate analyses (P=0.025).CONCLUSIONS: Overexpression of IGF1R was found to be directly correlated with shorter DFS and OS as well as some clinicopathological features associated with adverse prognosis such as higher Ki67 index, mitotic count, tumor grade, presence of geographic necrosis, HER2 positivity, ER negativity, HER2+ molecular subtype, histological tumor type of IDC rather than ILC. Thus, IGF1R might be considered as an useful target for comprehensive future anti-tumor therapy investigations. Additionally, using IGF1R as well as Ki67 as a part of routine pathology practice might be fruitful in breast cancer therapy and prediction of prognosis.
Keywords: Breast Carcinoma; IGF1R; Insulin-Like Growth Factor-1 Receptor; Immunohistochemistry; Prognosis